After the Berlin Wall : a History of the EBRD, Volume 1 - Kilpatrick, Andrew (Central European University Press, 2020)
"After the Berlin Wall tells the inside story of an international financial institution, the European Bank for Development and Reconstruction (EBRD), created in the aftermath of communism to help the countries of central and eastern Europe transition towards open market-oriented democratic economies. The first volume of a history in two parts, after the Berlin Wall charts the EBRD's life from a fledgling high-risk, start-up investing in former socialist countries from 1991 to become an established member of the international financial community, which (as of April 2020) operates in almost 40 countries across three continents. This volume describes the multilateral negotiations that created this cosmopolitan institution with a 'European character' and the emergence of the EBRD's unique business model : a focus on the private sector and a mission to deliver development impact with sustainable financial returns. The author recounts the challenges that 'transition' countries faced in moving from a defunct to a better economic system and maps the EBRD's response to critical events, from the dissolution of the Soviet Union, to the safe confinement of the Chernobyl disaster site, the debt default in Russia and the onset of the global financial crisis in 2008"--